Acute Consumption of Bordo Grape Juice and Wine Improves Serum Antioxidant Status in Healthy Individuals and Inhibits Reactive Oxygen Species Production in Human Neuron-Like Cells. (1st March 2018) - Copetti, Cristiane; Franco, Fernanda Wouters; Machado, Eduarda da Rosa; Soquetta, Marcela Bromberger; Quatrin, Andréia; Ramos, Vitor de Miranda; Moreira, José Cláudio Fonseca; Emanuelli, Tatiana; Sautter, Cláudia Kaehler; Penna, Neidi Garcia
Abstract : Few studies investigated the biological effects of American grape cultivars. We investigated the metabolic response after acute consumption of grape juice or wine from Bordo grapes ( Vitis labrusca ) in a placebo-controlled crossover study with fifteen healthy volunteers. Blood samples were collected 1 hour after the intake of 100 mL of water, juice, or wine to measure TBARS, ABTS, FRAP, glucose, and uric acid levels. To evaluate differences in cellular response, intracellular reactive species production (DCFH-DA) and metabolic mitochondrial viability (MTT) were assessed after exposure of human neuron-like cells (SH-SY5Y) to juice or wine. Glycemia was reduced after juice or wine consumption, whereas blood levels of uric acid were reduced after juice consumption but increased after wine consumption. Juice and wine consumption reduced plasma lipid peroxidation and increased plasma antioxidant capacity (ABTS and FRAP assays). Furthermore, juice inhibited H2 O2 -induced intracellular production of reactive species (RS) and increased the viability of SH-SY5Y cells. In contrast, wine (dealcoholized) exhibited a per se effect by inducing the production of RS and reducing cell viability. These results indicate a positive impact of acute consumption of Bordo juice and wine on human oxidative status, whereas only juice had protective effects against oxidative stress-induced cytotoxicity.